2021
DOI: 10.1080/10717544.2021.2021323
|View full text |Cite
|
Sign up to set email alerts
|

Development of a naringenin microemulsion as a prospective ophthalmic delivery system for the treatment of corneal neovascularization: in vitro and in vivo evaluation

Abstract: Naringenin, a flavonoid, possesses antiangiogenic potential and inhibits corneal neovascularization (CNV); however, its therapeutic use is restricted due to poor solubility and limited bioavailability. In this study, we developed a naringenin microemulsion (NAR-ME) for inhibiting CNV. NAR-ME formulation was composed of triacetin (oil phase), Cremophor RH40 (CRH40), PEG400, and water, its droplet size was 13.22 ± 0.13 nm with a narrow size distribution (0.112 ± 0.0014). The results demonstrated that NAR-ME rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The observed results confirmed that the LCZ-NE could significantly enhance LCZ release compared to the pure drug suspension. The ability of NEs to increase the dissolution of poorly aqueous-soluble drugs has been observed in previous published research [ 43 ]. The in vitro release kinetics of LCZ from the LCZ-NE were analyzed using different mathematical models, with pure LCZ used as a control.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The observed results confirmed that the LCZ-NE could significantly enhance LCZ release compared to the pure drug suspension. The ability of NEs to increase the dissolution of poorly aqueous-soluble drugs has been observed in previous published research [ 43 ]. The in vitro release kinetics of LCZ from the LCZ-NE were analyzed using different mathematical models, with pure LCZ used as a control.…”
Section: Resultsmentioning
confidence: 81%
“…In order to study the thermodynamic stability of the LCZ-NE, three freeze/thaw rounds were performed on freshly prepared LCZ-NE [ 43 ]. In Brief, the LCZ-NE was added into a transparent glass bottle and sealed, then stored in a refrigerator at −20 for 18 h. After that, the bottle was removed, kept at room temperature (25 ) for 18 h and returned to the refrigerator with the same previous temperature for another 18 h, in order to fulfill the second cycle.…”
Section: Methodsmentioning
confidence: 99%
“…The drug release from LORA-NLCs formulae was fitted in several mathematical models to identify the mechanism of release. The values of the regression coefficient imply that the Higuchi model was the best fit for the LORA-NLCs release profile (Ma et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several plant extracts, including epigallocatechin gallate (EGCG), 42 celastrol, 43 curcumin, 44 kaempferol 45 and naringenin, 46 have been found to inhibit experimental CNV. The plant extracts mentioned above (except EGCG, which is a water-soluble active ingredient) are all hydrophobic molecules.…”
Section: Strategies For the Treatment Of Cnv And Corresponding Limita...mentioning
confidence: 99%
“…Other plant extracts, including celastrol, curcumin, kaempferol and naringenin, are hydrophobic molecules that limit their clinical use. In response, they were encapsulated in micelles, 43 NPs, 44 GNPs 45 and microemulsions 46 respectively to greatly improve their water solubility while still retaining their activities in CNV therapy.…”
Section: Applications Of Ons In Cnv Therapymentioning
confidence: 99%